2017
DOI: 10.15388/ekon.2017.1.10663
|View full text |Cite
|
Sign up to set email alerts
|

Trade Openness, Inequality and Poverty in Latin American Countries

Abstract: Abstract. Globalization has quickened, especially during the past three decades, due to technological, institutional, legal and political developments in the world. During this process, many countries reduced or removed the barriers on the cross-country flows of goods, services and capital, and the global trade volume increased substantially. Therefore, openness-oriented policies have led many social and economic implications for the national economies. In this regard, this study investigates the interaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…The finding is in line with theoretical propositions linking trade to poverty alleviation through transmission mechanisms such as economic growth (Shuaibu, 2017) skill-biased technological change (Nissanke & Thorbecke, 2010) changes in prices faced by households (Winters et al, 2004), employment and wages (Goldberg & Pavcnik, 2007b). Empirically this is in tandem with several studies (including (Bayar & Sezgin, 2017;Kis-Katos & Sparrow, 2015;Onakoya et al, 2019;Zahonogo, 2016)).…”
Section: Generalised Methods Of Moments (Gmm) Estimation Resultssupporting
confidence: 83%
“…The finding is in line with theoretical propositions linking trade to poverty alleviation through transmission mechanisms such as economic growth (Shuaibu, 2017) skill-biased technological change (Nissanke & Thorbecke, 2010) changes in prices faced by households (Winters et al, 2004), employment and wages (Goldberg & Pavcnik, 2007b). Empirically this is in tandem with several studies (including (Bayar & Sezgin, 2017;Kis-Katos & Sparrow, 2015;Onakoya et al, 2019;Zahonogo, 2016)).…”
Section: Generalised Methods Of Moments (Gmm) Estimation Resultssupporting
confidence: 83%
“…The finding is in line with theoretical propositions linking trade to poverty alleviation through transmission mechanisms such as economic growth (Shuaibu, 2017) skill-biased technological change (Nissanke & Thorbecke, 2010) changes in prices faced by households (Winters et al, 2004), employment and wages (Goldberg & Pavcnik, 2007b). Empirically this is in tandem with several studies (including (Bayar & Sezgin, 2017;Kis-Katos & Sparrow, 2015;Onakoya et al, 2019;Zahonogo, 2016)).…”
Section: Generalised Methods Of Moments (Gmm) Estimation Resultssupporting
confidence: 83%
“…Therefore, we could say that public health spending has a greater effect on reducing poverty in countries with poor governance than in countries with good governance. As shown in Figure 1 Bayar & Sezgin (2017), concluding that the relationship between trade and poverty is not significant.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, trade grows the economy of a country, and economic growth leads to optimal revenue. Higher expenditure proportionate to the need to alleviate poverty is possible supposing the income of the country is higher Bayar & Sezgin (2017). have found that trade openness and improvement in the financial sector play a significant role in reducing poverty.…”
mentioning
confidence: 99%